The influence of linear and nonlinear pedagogies on movement exploration of a weightlifting skill - Riki S. Lindsay; John Komar; Jia Yi Chow; Aden Kittel; Paul Larkin; Michael Spittle (Acta Psychologica)
The influence of linear and nonlinear pedagogies on movement exploration of a weightlifting skillTraditional linear pedagogy (LP) is frequently criticised for being overly restrictive and limiting the development of individualised movement solutions. This has led to the recommendation of less restrained approaches, such as nonlinear pedagogy, to foster broad, self-organised movement exploration. However, limited research has investigated the nature of exploration strategies between LP and NLP approaches. This study aimed to investigate the dynamics of exploration under LP and NLP approaches. A four-week intervention involving 16 novice weightlifters demonstrated that NLP and LP facilitated similar performance outcomes, challenging the assumption that structured approaches inhibit movement exploration. Cluster analyses revealed that NLP enabled broader exploration, while LP narrowed exploration to certain movements. Interestingly, even within LP's structured limits, participants exhibited meaningful adaptive behaviour through minor movement adjustments. A significant interaction between exploration and learning was observed under NLP, indicating that exploration plays a functional role in performance improvement. These findings suggest that contrary to previous research, linear pedagogies do not necessarily deny learners the opportunity to exploit functional movement variability during the learning process. This research offers new insights into the nuanced interplay between exploration and adaptation when engaged in different learning approaches.